DEONTOLOGI PEMERINTAHAN DAERAH DI INDONESIA (Oase Akuntabilitas Politik dalam Perspektif Partisipasi Politik) - IRWAN NOOR, IRWAN NOOR (Politika: Jurnal Ilmu Politik, 2010)
AbstractAccountability is often believed to be the embodiment of democratic society, so oftenrelied upon by local government. However, by criticizing the Law 32/2004, the need to furtherunderstanding of the concept, particularly with the Development state Theory and RationalChoice Model in Political TheoryKeyword: Accountability, Political Participation